Assessing the Islamic Values in the Halal Supply Chain of the Poultry Industry - Emi Normalina Omar; Harlina Suzana Jaafar; Muhamad Rahimi Osman; Nasruddin Faisol (International Journal of Supply Chain Management, 2019)
The values in our daily life are important as the values play a role in influencing our principles and behaviours, and positive values could create good behaviour and a happy living. Thus, values in Islam are essential as those act as a guide for Muslims to be the good believers and capable in forming the better societies. These values are based on the Shariah principles which can be found in the Holy Qur’an, which dominantly enacted as the main reference of foundation for Muslims in present time and the Hereafter. Occasionally, Muslims do not realise that the good things that they do in their daily activities are considered as good values from the Islamic perspective, i.e. Islamic values. The present business environment of the food supply chain, particularly the poultry industry has been chosen in this study due to the fact of highest food consumption of Malaysian in poultry and poultry based products. This study found that research which assessing the Islamic values and halal supply chain has received relatively little attention in the literature. Therefore, this study attempts to fill this void by assessing the Islamic values in the halal supply chain of the poultry industry. By using a qualitative approach, data was collected from in-depth interviews of a case study. The case study of poultry supply chain is focused on the initial stage of supply chain i.e. farm. Therefore, this study found six Islamic values which exist in the halal supply chain.